Membangun Ekonomi Nasional dengan Landasan Akhlaq Islami dan Hukum Islam - Edy, Sarwo; RWulandari, Septiayu; AbdulHafizh, Daffa (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
Sustainable national economic development requires a strong foundation, not only technically and policy-wise but also ethically. This article discusses the importance of building a national economy based on Islamic morals and laws. The application of Islamic moral values in economic practices can create a more inclusive and sustainable economy. Similarly, Islamic law provides guidelines for transactions and fair wealth distribution. By integrating these principles, society can create a balanced and just economic environment, where blessings and prosperity are evenly distributed. The research findings indicate that Islamic moral and legal economic concepts, such as joint ownership, distributive justice, and prohibition of usury, are highly relevant in the context of national economic development. Some countries have attempted to implement Islamic economic principles in their national policies, though challenges remain. These challenges include mismatches with the dominant global economic system, lack of public understanding and awareness of Islamic moral values, and difficulties in balancing Islamic economic principles with modern economic needs. Despite these challenges, building a national economy on Islamic morals and laws holds significant potential benefits, including a more stable and sustainable financial system, reduced economic inequality, improved public welfare, and strengthened social and moral bonds within society.